Schisandrin C: an active compound from the fruit of Schisandra chinensis in anti-inflammation and anti-oxidation: Anti-inflammation and anti-oxidation effects of schisandrin C - Kim, Tae Won; Hwang, Seonhwa; Park, Min Seo; Kim, Hye Kyung; Park, Min Hi (Cellular and Molecular Biology, 2023)
Inflammatory responses are involved in various diseases, such as insulin resistance, atherosclerosis, and hypogonadism. This study investigates the effects of SCE on anti-inflammation and molecular mechanisms in LPS-induced macrophages. RAW 264.7 macrophage cells were treated with LPS for 24 hr, followed by SCE, schisandrin C (Sch C) (1, 10, and 100 μM), and gomisin N (GN) (1, 10, and 100 μM) for 24 hr. Gene expression levels of pro-inflammatory cytokines were measured by qPCR. Protein expression of NLPR3 inflammasome was examined by western blot analysis. The expression levels of pro-inflammatory cytokines, including IL-1β, IL-6, and TNFα, were significantly reduced after SCE treatment. Sch C significantly inhibits these pro-inflammatory cytokines, while GN suppresses only IL6. Furthermore, Sch C significantly prevented the activation of NLRP3 inflammasome complexes such as NLRP3 and caspase-1. Sch C is the major active compound of SCE on anti-inflammation through attenuation of NLRP3 inflammasome.